Cretaceous sauropod diversity and taxonomic succession in South America - de Jesus Faria, Caio Cesar (2015)
The South American sauropod dinosaurs fossil record is one of the world's most relevant for their abundance (51 taxa) and biogeographical implications. Their historical biogeography was influenced by the continental fragmentation of Gondwana. The scenery of biogeographic and stratigraphic distributions can provide new insight into the causes of the evolution of the sauropods in South America. One of the most important events of the sauropods evolution is the progressive replacement of Diplodocimorpha by the Titanosauriformes during the early Late Cretaceous. The fluctuation of the sea levels is frequently related to the diversity of sauropods, but it is necessary to take into account the geological context in each continent. During the Maastrichthian, a global sea level drop has been described; in contrast, in South America there was a significant rise in sea level (named 'Atlantic transgression') which is confirmed by sedimentary sequences and the fossil record of marine vertebrates. This process occurred during the Maastrichtian, when the hadrosaurs arrived from North America. The titanosaurs were amazingly diverse during the Late Cretaceous, both in size and morphology, but they declined prior to their final extinction in the Cretaceous/Paleocene boundary (65.5Yrs).